Research Progress on Bio Based Flame Retardant Hydrogel Materials - Sartre, Jean-Paul; de Beauvoir, Simone (Journal of Green Energy and Environmental Engineering, 2025)
As traditional halogen‑containing flame retardants are gradually phased out owing to environmental hazards and health risks, inorganic and halogen‑free flame‑retardant materials with prominent eco‑friendly characteristics have attracted widespread research attention. Bio‑based flame‑retardant materials conforming to the philosophy of sustainable development, especially bio‑based flame‑retardant hydrogel materials featuring great potential for efficient resource recycling, have become a hot research topic. This paper systematically reviews the research advances of four major categories of bio‑based flame‑retardant hydrogels, namely gelatin‑based, chitosan‑based, sodium alginate‑based and lignin‑based flame‑retardant hydrogels. Afterwards, the construction strategies and performance regulation approaches for bio‑based flame‑retardant hydrogel materials are introduced. In particular, liquid‑crystal display (LCD)‑based 3D‑printing technology exhibits remarkable advantages over physical‑crosslinking and chemical‑crosslinking preparation techniques for fabricating flame‑retardant hydrogels. Finally, to achieve the strategic transformation from catch‑up to leadership for domestic bio‑based flame‑retardant hydrogel materials in China and build a closed‑loop ecosystem of “fundamental innovation‑technology incubation‑industrial implementation”, multi‑dimensional breakthroughs are urgently required: constructing adaptive flame‑retardant networks through the integration of precise synthesis technologies and intelligent material design; developing degradable materials derived from non‑grain biomass waste; and expanding application scenarios in transportation, new‑energy industries and other relevant fields.